PEMBUATAN INSTRUMENT AUDIO MUSIK BERBASIS KOMPUTER DENGAN MENGGUNAKAN SOFTWARE FRUITY LOOPS 8 - Sudar Yanto; Aqwam Rosadi Kardian (Jurnal Sistem Informasi, 2010)
Knowledge to play music to produce different sounds good to hearexperience and made a few times. Thousands and perhaps millions of youngpeople who have the talent to play music. Give the expected solution for smallchildren or people who like to play music, promote your music with the help ofcomputer games without the need for a tool. Written by the author's in the formof a training manual for the reader to more easily understand. Development ofcomputers provide opportunities for people who love the music until she willdevelop a game to learn and train The role of information and computertechnology is growing so fast recently. Even e-Government and e- commerce isbuilt to give a new dimension of life in Indonesia. Now people have to usecomputers in everyday life. In music, to get a good job and gave birth to abrilliant musical artist, now the computer is also very influential. Fruity Loops 8is to help the musicians or someone who likes playing music can help in makingmusic without having to possess, have and can use the instrument